Implementation of Synthetic Aperture Radar Active Decoy Hardware (Advances in Military Technology, 2022)
As a result of the military's use of synthetic aperture radar (SAR), it has become necessary to use jamming techniques to protect sensitive sites of friendly forces from being intercepted by SAR. To combat SAR sensors, two jamming techniques are typically available: noise jamming and deceptive jamming. In this paper the design and hardware implementation of a proposed active decoy which works as deceptive jamming system, is achieved using field programmable gate array (FPGA). The performance of the developed system is evaluated by SystemVue. 2015.01, using “hardware in the loop” methodology.
Keywords: active decoy; FPGA; SAR